Influence of phase transition on shock-induced spallation in nanocrystalline iron - Gunkelmann, Nina (2015)
Intense shock waves may lead to spallation of the sample. Recent experiments show differences of shock spallation in iron depending on whether the samples underwent the pressure-induced bcc-hcp phase transformation or not. In this study, we perform molecular dynamics simulations of shock-induced spallation in polycrystalline iron. Our results show that the phase transformation decreases the probability of multiple spallation and crack formation. In agreement with experiments, the phase transformation changes the surface morphology showing smoother spallation surfaces.